High risk of breast cancer in women with biallelic pathogenic variants in CHEK2 - Rainville, Irene (Breast Cancer Res Treat, 2020)
PURPOSE: Compared to breast cancer risk genes such as BRCA2, ATM, PALB2, and NBN, no defined phenotype is currently associated with biallelic pathogenic variants (PVs) in CHEK2. This study compared the prevalence of breast and other cancers in women with monoallelic and biallelic CHEK2 PVs. METHODS: CHEK2 PV carriers were identified through commercial hereditary cancer panel testing (09/2013–07/2019). We compared cancer histories of 6473 monoallelic carriers to 31 biallelic carriers. Breast cancer risks were estimated using multivariate logistic regression and are reported as odds ratios (OR) with 95% confidence intervals (CI). RESULTS: Breast cancer frequency was higher among biallelic CHEK2 PV carriers (80.6%, 25/31) than monoallelic carriers (41.2%, 2668/6473; p < 0.0001). Biallelic carriers were more likely to be diagnosed at or before age 50 (61.3%, 19/31) and to have a second breast cancer diagnosis (22.6%, 7/31) compared to monoallelic carriers (23.9%, 1548/6473; p < 0.0001 and 8.1%, 523/6473; p = 0.0107, respectively). Proportionally more biallelic carriers also had any cancer diagnosis and > 1 primary diagnosis. Compared to women with no PVs, biallelic PV carriers had a higher risk of developing ductal invasive breast cancer (OR 8.69, 95% CI 3.69–20.47) and ductal carcinoma in situ (OR 4.98, 95% CI 2.00–12.35) than monoallelic carriers (OR 2.02, 95% CI 1.90–2.15 and OR 1.82, 95% CI 1.66–2.00, respectively). CONCLUSIONS: These data suggest that biallelic CHEK2 PV carriers have a higher risk for breast cancer, are more likely to be diagnosed younger, and to have multiple primary breast cancers compared to monoallelic carriers. Biallelic carriers also appear to have a higher risk of cancer overall. Therefore, more aggressive management may be appropriate for women with biallelic PVs in CHEK2 compared with current recommendations for monoallelic carriers.